2001
DOI: 10.1097/00007890-200108270-00012
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function Before and Long After Liver Transplantation in Children1

Abstract: Renal function is reduced by OLT and decreases further during the first years after OLT. Patients with metabolic disorders and those on antihypertensive treatment have the lowest GFR. Determination of GFR by the formula creatinine clearance is inaccurate in children after liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 33 publications
11
63
0
Order By: Relevance
“…1,34,35 In the present study, reduced GFR 36 and histologic abnormalities on sequential renal biopsies 37 were absent, and except for the relatively higher urinary ␤ 2 -globulin concentrations in patients receiving Cy, there were no other indications of tubulointerstitial dysfunction. 38,39 Lower doses and trough levels of Cy employed in our patients may account for these findings.…”
Section: Discussionsupporting
confidence: 43%
“…1,34,35 In the present study, reduced GFR 36 and histologic abnormalities on sequential renal biopsies 37 were absent, and except for the relatively higher urinary ␤ 2 -globulin concentrations in patients receiving Cy, there were no other indications of tubulointerstitial dysfunction. 38,39 Lower doses and trough levels of Cy employed in our patients may account for these findings.…”
Section: Discussionsupporting
confidence: 43%
“…Although these findings are in agreement with previous reports, they must be taken in the context of our study limitations. 8,17 In our population, time since transplant and cyclosporine immunosuppression are strongly collinear. Although the multivariate model incorporating immunosuppression and excluding time since transplant proved to be the more predictive, the likelihood of continued overlap between these two factors should not be minimized, nor should the role of time since transplant be discounted.…”
Section: Resultsmentioning
confidence: 98%
“…The relation between renal function (GFR or serum creatinine) at 1 year and long-term renal function has been described in adults and suggested in children. 6,7,14,17 A more controversial issue is the question of continuing decline in GFR after the first year after transplant. 14,18 Our data suggest that patients who have longterm renal dysfunction show a progressive decline in mGFR after the first posttransplant year, whereas patients with normal long-term renal function are more likely to have a stable, or improving, mGFR after the first posttransplant year.…”
Section: Resultsmentioning
confidence: 99%
“…Because serum creatinine, serum urea, and calculated GFR levels are not sufficiently sensitive markers of renal function in children (15), measurement of GFR likely serves as the best method to monitor kidney function after OLT. Indeed, GFR measurement performed at the 10-year anniversary revealed that renal dysfunction was the most common comorbidity in our group and would have been missed by reliance on serum creatinine levels or calculated GFR alone.…”
Section: Discussionmentioning
confidence: 99%